Influence assessment of new Inner Tube Porous Brick with absorbent concrete on urban floods control. (December 2022) - Luo, Pingping; Liu, Liming; Wang, Siting; Ren, Baiming; He, Bin; Nover, Daniel
Abstract: As a part of low impact development (LID) measures, modifying the design of Inner Tube Porous Bricks (ITPB) may improve the functionality of the pavement to prevent urban floods. Absorbent concrete (AC) with different Super Absorbent Polymers (SAP) concentration was used as the brick materials to adsorb 311–376 l water per m 3 AC after 120 min, and the hydraulic conductivity was calculated to vary between 34.59 mm/h and 74.8 mm/h for different ACs. The Storm Water Management Model (SWMM) is used here to simulate the influence of the ITPB on urban floods. When the return period (P) equals 100 years, the peak inflow of drainage networks can be decreased from 254.55 l/s to 91.12 l/s and the stormwater could be infiltrated 52.49 mm in low permeability areas (e.g. clay) by ITPB pavement. ITPB can be used as a new LID pavement in clay areas or be used to mitigate urban floods of long return period storms. Which should be noted is that the declared values about the simulation are valid in the study areas, further research is needed on the applicability of ITPB to the overall world. Graphical Abstract: ga1 Highlights: Super Absorbent Polymers enhanced the water absorption capacity of concrete. The ITPB pavement has an apparent effect on reducing flood peak. The ITPB pavement performs better for preventing long return period storms. The ITPB pavement can infiltrate stormwater more efficient in clay area.